PorV factor of the type IX secretion system and PosF porin act as adhesins in Riemerella anatipestifer infection - Sen Li; Yanhua Wang; Congran Ning; Rongkun Yang; Yaxin Wu; Xu Cheng; Keke Ren; Minghua Huang; Xiong Liu; Naiji Zhou; Wanpo Zhang; Sishun Hu; et al. (Veterinary Research)
Abstract Riemerella anatipestifer infection is a critical disease that is a major threat to the poultry industry worldwide. The adhesion and invasion of host cells are key steps in the primary stages of bacterial infection. However, the outer membrane proteins that mediate these events in R. anatipestifer are poorly characterized. In this study, the PorV and PosF proteins, as well as the previously described OMP71 protein, were identified as important mediators of the adhesion and invasion of duck embryo fibroblast (DEF) cells by R. anatipestifer. Affinity chromatography-based surface proteomics was used to screen for adhesion proteins. The surface proteins on DEF cells were labelled with biotin-avidin to enrich for outer membrane proteins of R. anatipestifer, which generated 11 candidate proteins that were tested further. Protein adhesion and blocking assays and polyclonal antiserum inhibition analysis revealed that the PorV, PosF, and OMP71 proteins are adhesion factors. Knockout of porV or posF reduced the adhesion and invasion of R. anatipestifer in DEF cells. Moreover, the pathogenicity of the mutant strains was significantly attenuated, which supports the hypothesis that PorV and PosF are important virulence factors required for the pathogenicity of R. anatipestifer. The PorV protein is a key component of the type IX secretory system and is responsible for transporting effector substrates to the extracellular environment, whereas PosF belongs to the porin superfamily of barrel-shaped transmembrane proteins. This is the first description that PorV is an adhesin involved in host‒microbial interactions, which represents a breakthrough in pathogenicity studies of R. anatipestifer and other members of Flavobacteriaceae.